The effects of robusta coffee on tooth discolouration - Chu Chin Sin; Ayu Trisna Hayati; Endang Sukartini (Universitas Padjadjaran, 2012)
Introduction: One of the most frequent dental problems that confronted dentist is tooth discoloration which can cause significant cosmetic problems. Extrinsic tooth discoloration occurs when stain forms on the tooth surface or in the pellicle and the common causes of extrinsic tooth discoloration is coffee. Robusta coffee contains high level of chromogenic compound which can incorporate itself into the acquired pellicle and tannic acids that can denature the pellicle protein and increase its stain ability. The purpose of this experiment was to investigate the tooth discoloring effect of Robusta coffee solution. Methods: This research type was a true experiment (in vitro) using 30 samples of maxillary first premolar whose roots had been cut until the CEJ. Samples were divided into 2 groups (which are soaked in Robusta coffee solution and the other in mineral water) of 15, with a frequency of three times daily for seven days. The difference in tooth color changes was measured by using a spectrophotometer. Results: This research was analyzed by using t-test and there was a significant difference between the two groups (p-value≤0.00). Conclusion: Robusta coffee effected to tooth discoloration.